The Feasibility of Property Rights for Genome Owners in Human-Centered Genetic Research Contracts - Zahra Khosrojerdi; Mohammadreza Gholampour; Seyed Mohsen Hosseini poua (آموزه‌‌های فقه مدني)
Based on findings from a comparative study of Islamic law and other legal systems, the views of religious scholars, similar to the approaches of various countries, regarding the recognition of ownership rights for patients or participants in human genome research projects have been inconsistent and variable. These inconsistencies stem not only from the connection of these contracts to human rights issues, such as the right to health and equitable access to gene therapy and genetic medicine, but also from their association with the commercial utilization of discoveries derived from human genetic resources. The gap between the rapid advancement of genetic science and the absence of a unified legal framework addressing ownership rights between researchers and donors has impacted individuals' claims and rights to the economic benefits derived from human biological materials. This gap has also created barriers to research and the development of the genomics industry. Evidently, the recognition of ownership rights in such research, like other legal rights, is not absolute, and legislators must limit these rights to ensure public order. Therefore, by examining the approaches taken toward the extent of human biological control and the implications of these approaches on research contracts and human genome transfer, this study aims to clarify an acceptable theory under Iranian law.